MONITORING AND CONTROL OF DOMESTIC DC LOADS CONNECTED TO SINGLE INPUT MULTIPLE OUTPUTS (SIMO) DC–DC CONVERTER USING IoT (The Transactions of the Nigerian Association of Mathematical Physics, 2024)
Photovoltaic (PV) power generation, utilization and home automation and domestic loads control are exciting fields that are exploding the recent technologies. Internet of Things (IoT) provides an attractive and technological platform to connect the two and make home automation and domestic energy utilization easier and attractive. This paper presents the use of IoT-based control topology to monitor and control power distribution and consumption by DC loads connected to single-input multiple outputs (SIMO) DC-DC converter, thereby reducing leakages, enhancing performance and reducing human efforts. A SIMO converter was first developed and integrated with the IoT/Raspberry Pi control topology, which enable the user to monitor and control power scheduling and load forecasting via an android app. The two systems were developed and tested with a reliable and convincing solution to home automation and loads management. Demands and supply were recorded by the user via mobile app created to monitor the management and control. The recorded data are plotted and shows how the two react to changes in solar energy supply and demands by the loads.